Atlantic crossings : social politics in a progressive age - Rodgers, Daniel T. (ACLS Humanities E-Book (Series), 1998)
On a narrative canvas that sweeps across Europe and the United States, Daniel T. Rodgers retells the story of the classic era of efforts to repair the damage of unbridled capitalism. He reveals the forgotten international roots of such innovations as city planning, rural cooperatives, modernist architecture for public housing, and social insurance, among other reforms. From small beginnings to reconstructions of the new great cities and rural life, and to the wide-ranging mechanics of social security for working people, Rodgers finds the interconnections, adaptations, exchanges, and even rivalries in the Atlantic region's social planning. He uncovers the immense diffusion of talent, ideas, and action that were breathtaking in their range and impact.